2014
DOI: 10.1016/j.jconrel.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vivo antioxidative activity of redox nanoparticles by using a developing chicken egg as an alternative animal model

Abstract: Antioxidants have been demonstrated to exert beneficial effects as pharmacotherapies for cardiovascular diseases. The in vitro systems generally employed to evaluate antioxidants, however, are limited by having no appreciable in vivo redox status of the antioxidants. Therefore, we used our developing chicken egg model to evaluate the in vivo antioxidative activity of a redox nanoparticle possessing 2,2,6,6-tetramethylpiperidine-1-oxyl (RNP(O)). The 2,2'-azobis(2-methylpropionamidine) dihydrochloride (AAPH) eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In the late case, ROS may not only kill invading pathogens and microbes but also damage the components of the cell, including proteins, lipids, carbohydrates, and DNA [ 16 ]. Overwhelming evidence indicates that oxidative stress is involved in the pathophysiology of the wide array of human diseases, including cancer [ 17 ], cardiovascular disease [ 18 ], AIDS [ 19 ], diabetes mellitus [ 20 ], and neurodegenerative disorders such as aging, Parkinson's disease, and Alzheimer's disease [ 21 , 22 ].…”
Section: Free Radical Oxidative Stress and Cellular Antioxidant mentioning
confidence: 99%
“…In the late case, ROS may not only kill invading pathogens and microbes but also damage the components of the cell, including proteins, lipids, carbohydrates, and DNA [ 16 ]. Overwhelming evidence indicates that oxidative stress is involved in the pathophysiology of the wide array of human diseases, including cancer [ 17 ], cardiovascular disease [ 18 ], AIDS [ 19 ], diabetes mellitus [ 20 ], and neurodegenerative disorders such as aging, Parkinson's disease, and Alzheimer's disease [ 21 , 22 ].…”
Section: Free Radical Oxidative Stress and Cellular Antioxidant mentioning
confidence: 99%
“…The persistent nature of these nitroxides originates from: (1) electron delocalization along the N-O bond and (2) the stabilization against combination and disproportionation by the four α-methyl groups adjacent to the N-O centre. Nitroxides have many applications, including as spin probes and spin labels, 1,2 superoxide dismutase mimics, 3,4 antioxidants [5][6][7] and control agents in 'living' radical polymerization. 8,9 Early work, as summarised by Rozantsev, 10 focussed on the comprehensive synthesis of functional nitroxides, including TEMPO, pyrrolidine (PROXYL) and pyrroline radicals as well as various derivatives, and their applications in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Embryonated chicken eggs as an experimental model in fungal infection research have been shown to be effective for evaluating the virulence and pathogenicity of experimental infections by Aspergillus fumigatus and Candida albicans . Indeed, many studies have demonstrated that the developing chicken egg is a useful model for the in vivo evaluation of antioxidative, antiviral and anti‐angiogenic activities, as well as in drug toxicology studies …”
Section: Discussionmentioning
confidence: 99%